Application of Circular-Economy Concept to Pre-Consumer Apparel Waste Management in Sri Lanka (Proceedings of the World Conference on Waste Management, 2021)
Sri Lanka is one of the major apparel manufacturers in South Asian region, which results to generate more pre-consumer apparel waste. Many of the past studies have shown that absence of acceptable waste management systems, to manage massive amounts of pre-consumer apparel waste generated has made the waste management issue complicated. In Sri Lanka, it is likely that 25% of apparel waste are reused and recycled while landfilling and incinerating the rest which have adverse environmental impacts. This ‘take, make, consume and discard’ principle is known as the basis of Linear Economy (LE) and due to the series of challenges and the underlying limitations of it, the concept of Circular Economy (CE) is considered as a solution for harmonising ambitions for economic growth and environmental protection. Lean Manufacturing, Green Supply Chain Management, Extended Producer Responsibility and 3R Concept are the waste management approaches that have been used to implement the concept of CE in pre-consumer apparel waste management. The aim of this research is to enhance the effective pre-consumer apparel waste management practices through CE concept. This paper will present implementation tools of aforementioned waste management concepts in order to implement the concept of CE effectively. Holistic, multiple case studies have been adopted as the research strategy under qualitative approach, accordingly 08 semi-structured interviews were conducted from four leading apparel manufacturing organisations in Sri Lanka.  Through the study it was identified that Kaizen, Kanban, partnering with brands and suppliers into sustainable manufacturing and polluter pays principle are some of the implementation tools which needs to be implemented and further enhanced for the effective implementation of CE concept within the Sri Lankan context.
Keywords: pre-consumer apparel waste; circular economy; linear economy; waste management